Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1038/nbt0507-507
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of GM food—an experiment in six countries

Abstract: Bioscience, Biomedicine, Biotechnology and Society (BIOS) at the London School of Economics convened the group to design, analyse and interpret Eurobarometer 64.3 on Biotechnology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 8 publications
3
45
0
1
Order By: Relevance
“…However, there is also a strong indication that most people who bought food in the supermarket that contained a labeled GMO ingredient were not aware of having done so because they did not look at the label [63][64][65]. A study by Knight et al [66] addressed this problem by designing a natural quasi-experiment with road-side stalls selling fresh organic, conventional and 'fictitious' GM pest-resistant cherries (positively advertised as a 'spray-free GM product'); the products were sold by students in New Zealand and four different European countries. The study showed that consumers tended to buy more GM cherries when they were cheaper.…”
Section: Prior Field Experiments and Research Gapmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there is also a strong indication that most people who bought food in the supermarket that contained a labeled GMO ingredient were not aware of having done so because they did not look at the label [63][64][65]. A study by Knight et al [66] addressed this problem by designing a natural quasi-experiment with road-side stalls selling fresh organic, conventional and 'fictitious' GM pest-resistant cherries (positively advertised as a 'spray-free GM product'); the products were sold by students in New Zealand and four different European countries. The study showed that consumers tended to buy more GM cherries when they were cheaper.…”
Section: Prior Field Experiments and Research Gapmentioning
confidence: 99%
“…The present field study follows the design of Knight et al [66] but addresses its limitations by combining the registration of revealed consumer preferences at the market stand with an ex-post questionnaire that reveals the prior political preference of the customer. Instead of a fictitious GM cherry variety, we used genuine GM corn as an ingredient of our corn bread.…”
Section: Innovative Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15] The studies showed that Europeans have a negative explicit attitude toward genetically modified food whereas their implicit attitude is more positive. 16 It is suggested that these positive attitudes might enhance the behavioral intention of people toward the purchase of GM food.…”
Section: Gm Food On the Marketmentioning
confidence: 99%